INFLUENCE OF ROLLING ELEMENT VACUUM-PLASMA STRENGTHENING ON BEARING LIFE - S. Yu. Kotov; G. Ya. Belyaev (Наука и техника, 2014)
The paper investigates operational conditions of angular contact ball bearing МПЗ 6305 in automatic loaders and presents characteristics of its run-out due to usage conditions. An influence of vacuum plasma coating ZrN on bearing life characteristics has been researched in the paper. It has been established that an application of the mentioned coating significantly reduces the probability of bearing rolling elements corrosion, practically excludes their abrasive wear and tear. Test investigations have made it possible to determine dependence of operational characteristics of strengthened bearings on coating thickness.